RANTAI NILAI KOMODITAS KOPI DALAM SKEMA PERHUTANAN SOSIAL: STUDI KASUS KELOMPOK TANI HUTAN DI KINDANG, SULAWESI SELATAN - Rusadi, Nusrah; Gare, Kletus Florianus Sera; Marisi; Sari, Puspa (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study aims to analyze the coffee commodity value chain within the Community Forest (HKm) scheme in Kindang Subdistrict, Bulukumba Regency, South Sulawesi. The research focused on mapping the value chain structure, identifying key actors, and examining institutional challenges and strengthening strategies. A descriptive qualitative approach with a case study method was applied. Data were collected through in-depth interviews, field observations, and document reviews, and analyzed using a value chain analysis framework. The results revealed that the coffee value chain is still dominated by middlemen, while cooperatives have not functioned effectively as aggregators. Processing assets such as roasting and grinding machines remain underutilized due to limited technical skills and the absence of a collective production system. Farmers’ income falls in the moderate category (IDR 18.9–20.4 million per year), indicating low value addition. Recommended strategies include improving technical capacity, optimizing the use of processing equipment collectively, product diversification, developing digital marketing channels, and implementing quality-based incentive systems. These findings underscore the importance of institutional strengthening and product downstreaming to enhance the competitiveness of HKm coffee and improve farmers’ livelihoods.